KONSEP ALQURAN SEPUTAR DAKWAH BIL LISAN DI KELUARGA (TAFSIR QS.GHAFIR AYAT 28-34) - Irfa Afrini (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2023)
This journal aims to explore the implementation of oral propagation (Dawah Bil Lisan) within the family based on the exegesis of verses from Surah Ghafir ayat 28-34 in the Qur'an. The study examines the significance, strategies, and challenges involved in Dakwah Bil Lisan in the family unit. The research methodology employs a Qur'anic exegesis approach with qualitative analysis of Surah Ghafir ayat 28-34. Through a qualitative approach, the researcher examines the interpretations and insights of scholars to understand the principles and practical aspects of Dawah Bil Lisan in the family. In conclusion, this journal underscores the importance of Dawah Bil Lisan in the family based on the exegesis of Surah Ghafir ayat 28-34 in the Qur'an.